A Monetary Explanation of the Equity Premium, Term Premium, and Risk-Free Rate Puzzles - Bansal, Ravi; Coleman, Wilbur John (Journal of Political Economy, 1996)
This paper develops and estimates a monetary model that offers an explanation of some puzzling features of observed returns on equities and default-free bonds. The key feature of the model is that some assets other than money play a special role in facilitating transactions, which affects the rate of return that they offer. The model is capable of producing a low risk-free rate, a high equity premium, and an average positive relationship between maturity and term premium for default-free bonds. The model's implications for the joint distribution of asset returns, velocity, inflation, money growth, and consumption growth are also compared to the behavior of these variables in the U.S. economy.